The Influence of Innovation Climate on Creative Role Identity: The Mediating Role of Flow - Deng, Baijun; Cao, Jijuan; Huang, Jieqi; Wu, Jun (Frontiers in Psychology, 2022)
Creative role identity is an important antecedent of innovative behaviors. Both the mechanism of how external factors and individual factors affect the formation of creative role identity and details of this process have yet to be discovered. Based on data collected from 226 students in 6 classes at a university in Guangdong during the development of innovative projects, the influence of the innovation climate on the students’ creative role identity, especially the mediating effect of flow, was investigated. The results show that the innovation climate has a positive impact on creative role identity and that flow plays a partial mediating role in this relationship.